2015
DOI: 10.1515/snde-2014-0021
|View full text |Cite
|
Sign up to set email alerts
|

Testing the relationships between shadow economy and unemployment: empirical evidence from linear and nonlinear tests

Abstract: The aim of this paper is to empirically investigate the dynamic linkages between unemployment and shadow economy for 32 developing and developed countries for the period 1980 -2009 using parametric and non-parametric techniques. To this end, the Hansen and Seo (2002) threshold cointegration approach and the nonlinear causality test of Kyrtsou and Labys (2006) are applied to assess these relationships. Results obtained clearly do not support the view that unemployment and shadow economy are neutral with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
(111 reference statements)
1
6
0
Order By: Relevance
“…In comparison, the results of the shadow economy granger cause the unemployment rate to be statistically significant in all cases, excluding lag number 6 is not statistically significant. The finding of the panel study confirmed previous empirical studies by Saafi, Farhat and Mohamed(2015) and Sahnoun and Abdennadher(2019),They found mixed results of bidirectional causality between the two variables under investigation and unidirectional causality running from unemployment rate to the shadow economy. However, the present study found strong unidirectional causality running from the shadow economy to the unemployment rate.…”
Section: Pairwise Dumitrescu-hurlin Panel Causality Testssupporting
confidence: 89%
“…In comparison, the results of the shadow economy granger cause the unemployment rate to be statistically significant in all cases, excluding lag number 6 is not statistically significant. The finding of the panel study confirmed previous empirical studies by Saafi, Farhat and Mohamed(2015) and Sahnoun and Abdennadher(2019),They found mixed results of bidirectional causality between the two variables under investigation and unidirectional causality running from unemployment rate to the shadow economy. However, the present study found strong unidirectional causality running from the shadow economy to the unemployment rate.…”
Section: Pairwise Dumitrescu-hurlin Panel Causality Testssupporting
confidence: 89%
“…This approach has also become a prominent technique to study the linear causal relation between economic and financial variables. For example, it has been shown to be especially useful for exploring the relations between healthcare expenditure and GDP (Amiri and Ventelou (Nazlioglu and Soytas 2011), oil price shocks and stock market performance (Le and Chang 2015), terms of trade and economic growth (Jawaid and Raza 2013), energy consumption and output (Payne 2009, Menyah andWolde-Rufael 2010), debt and growth (Kemba and Khan 2016), the shadow economy and unemployment (Saafi et al 2015a(Saafi et al , 2015b, and economic growth and financial development (Abu-Bader andAbu-Qarn 2008, Wolde-Rufael 2009). Toda and Yamamoto (1995) used the modified Wald (MWALD) statistic for testing linear restrictions on the coefficients in an augmented VAR (k + d max ) model, where k is the optimal lag order in the VAR system and d max is the maximal order of integration in the model.…”
Section: A Granger Causality Approachmentioning
confidence: 99%
“…integration and economic growth are likely to exhibit a nonlinear pattern, and their joint dynamics imply a more complex than just a simple and stable relationship. In view of this, nonparametric analysis techniques are more suitable because they place direct emphasis on prediction without imposing a linear functional form (Saafi et al 2015a). The failure in previous literature to account for asymmetry and nonlinearity between financial integration and economic growth may have resulted in incorrect inferences about the existence/non-existence of the financial integration-growth relation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luo and Shang [73] stated that the unemployment rate serves as an index for describing the economy. Saafi and Farhat [74] and Saafi, Farhat, Mohamed, and Bel [75] proved that there is causality between unemployment and the unofficial sector.…”
Section: Hypothesismentioning
confidence: 99%